2020
DOI: 10.3892/ijo.2020.5043
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of GSG2 inhibits prostate cancer progression in�vitro and in�vivo

Abstract: Prostate cancer (PCa) is the second leading cause of cancer-related death among men worldwide. The present study aimed to investigate the role of germ cell-specific gene 2 protein (GSG2), also termed histone H3 phosphorylated by GSG2 at threonine-3, in the development and progression of PCa. GSG2 expression levels in PCa tissues and para-carcinoma tissues was detected by immunohistochemistry. The GSG2 knockdown cell model was constructed by lentivirus infection, and the knockdown efficiency was verified by qPC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 39 publications
(41 reference statements)
1
9
0
Order By: Relevance
“… 17 Yu et al reported, in prostate cancer cells, the inhibition of proliferation and migration and promotion of apoptosis, suggesting GSG2 as a tumor promotor in prostate cancer. 14 Similar functions could also be observed in pancreatic cancer 16 and gallbladder carcinoma. 16 In this study, our group discerned GSG2 as a novel regulator of ovarian cancer, thus a potential therapeutic target for treatment and prognostic indicator.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“… 17 Yu et al reported, in prostate cancer cells, the inhibition of proliferation and migration and promotion of apoptosis, suggesting GSG2 as a tumor promotor in prostate cancer. 14 Similar functions could also be observed in pancreatic cancer 16 and gallbladder carcinoma. 16 In this study, our group discerned GSG2 as a novel regulator of ovarian cancer, thus a potential therapeutic target for treatment and prognostic indicator.…”
Section: Discussionsupporting
confidence: 59%
“… 9 Survivin recognizes H3T3ph to bring the CPC (chromosomal passenger complex) to the centromere region, thereby promoting the metaphase arrangement of chromosomes and the cell cycle. 10–12 Although the function of GSG2 has not been clearly illustrated so far, some studies have shown that it plays a role as a cancer-promoting factor in various human tumors 13 such as prostate cancer, 14 gallbladder cancer 15 and pancreatic cancer. 16 Several studies have shown that its small molecule inhibitor CHR-6494 shows anti-proliferative activity in various tumor cell lines.…”
Section: Introductionmentioning
confidence: 99%
“…However, advanced PCa still lacks effective therapeutic strategies 3–5 . Thus, researchers are currently focused on inhibiting tumor progression to explore effective therapeutic strategies for PCa treatment 6,7 …”
Section: Introductionmentioning
confidence: 99%
“…After that, cells were colored using Giemsa Stain Kit (Abcam, ab150670) for 20 mins. Lasly, images of typical colony morphology were photographed and the the number of colonies in each conditions was counted under a Leica AM6000 microscope [41]. The colony formation assay was conducted with three independent assays in the same method.…”
Section: -Ethynyl-2-deoxyuridine (Edu) Incorporation Assaymentioning
confidence: 99%